THE CULTURAL RELEVANCE OF INDONESIAN PHRASEOLOGICAL UNITS AS CONTRASTED WITH POLISH - Przemysław Wiatrowski (Humaniora, 2015)
This article discusses Indonesian set phrases, a research area not previously investigated by Polish scholars. The aim is to analyze expressions which reveal the cultural specificity of the Indonesian speech community. Specifically, the author is concerned with two categories of multiword expressions. One of them is lexical combinations which preserve observations characteristic of the Indonesian speech community. These are reflected in a system of lexical connotations drawn upon in the process of semantic motivation of idioms. The other is expressions made up of units which are specific to Indonesian culture. The cultural relevance of Indonesian multi-word combinations is examined against the background of the Polish language. By examining research material derived from dictionaries of phrases and collocations and general dictionaries of the Indonesian language, the author provides insights into the way of thinking and responding to reality which is embedded in the language and in the collective experience of members of the Indonesian community.